Development and implementation of the cloud platform for tokenization of personal data of students - Shmatko, Oleksandr; Gamayun, Igor; Ivashchenko, Oksana (LLC SPC "InterConf", 2024)
The modern world is going through an important transitional period from the stage of informatization of important aspects of human activity to the stage of their digitization. Digital transformation means deep rethinking and reformatting of various spheres based on digital solutions and technologies. This process requires not only the maintenance of existing conditions for the development of advanced digital platforms and technologies, but also the creation of new opportunities for the birth of innovative solutions. In the context of the digital transformation of the educational sphere, a study was conducted on the use of blockchain technologies for the tokenization of educational resources and the analysis of the potential of their application in education. In the context of the digital transformation of the educational sphere, a study was conducted on the use of blockchain technologies for the tokenization of educational resources, thus the purpose of this study is to increase the confidentiality of educational data, their integrity and accessibility, as well as to ensure reliable exchange of this data between all interested parties due to design, development and implementation of software components of a cloud platform for tokenization of students' personal data based on blockchain technology. The object of the study includes systems for the transmission and processing of educational data, which ensure the exchange of data between all interested parties in the educational process. The subject of the research is the methods and means of designing and developing software components necessary for the creation and maintenance of platforms for the tokenization of students' personal data. These components include software for encryption, authentication, authorization, and mechanisms for fault tolerance and data recovery. This paper proposes a model of a cloud-based decentralized system for tokenization of students' personal data. The integration of blockchain technology into the education sector has great potential to strengthen trust and improve the quality of education services, as well as to create a new ecosystem of educational assets that are accessible and verified at the global level. The implementation of blockchain technology in the field of education requires the development of specialized software for issuing and verifying digital diplomas based on blockchain. The introduction of a cloud platform for tokenization of students' personal data promises a significant improvement in the processing and storage of educational documents, contributing to greater trust and transparency in the field of education.
Keywords: blockchain; personal data of students; cloud data storage; smart contracts; Ethereum; architectural model of cloud data tokenization platform